LEGAL CERTAINTY AND STANDARDS OF PROOF FOR JUDICIAL INTEGRITY: FROM SUBJECTIVE CONVICTION TO "DUE PROCESS" - Мудрицька, Катерина (SWorldJournal, 2026)
Introduction. The article examines the problem of assessing judicial integrity within the framework of judicial selection and evaluation procedures in Ukraine. For a long time, the absence of clear normative criteria for integrity enabled its interpretati